PERLINDUNGAN HUKUM BAGI WISATAWAN ASING DALAM PERJANJIAN ASURANSI KECELAKAAN - Alit Adiana, I Nyoman; Rai Djaja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum, 2013)
The legality of accident insurance agreement assigned toward foreigners is basically similar to common agreement. It is obliged to fulfill 4 conditions of legal agreement referring to Article 1320 Civil Act, namely: agreed to bind themselves; capability to make binding; there is an object agreed (certain thing); and due to reasonable matter or reasonable causal, although it is however condition determined in Article 1320 of specific Civil Act for accident insurance agreement for foreigners that is still unsatisfied yet, as it is additional regulations as per Article 251 Emergency Act, namely it must be a notification about anything concerning object situation that is known by the person assigned forinsurance object.Legal protection for foreigners in accident insurance agreement is taken over byService Loss Insurance Agency and Service Insurance Indonesia. Therefore, it covers selfaccident insurance for foreigners causing passing away, permanent injure and body injure.
Keywords: Foreigners, Accident Insurance Agreement